A crystal-structural study of Pauling–Corey rippled sheets. Issue 3 (17th December 2021) - Kuhn, Ariel J.; Ehlke, Beatriz; Johnstone, Timothy C.; Oliver, Scott R. J.; Raskatov, Jevgenij A.
Abstract : Following the seminal theoretical work on the pleated β-sheet published by Pauling and Corey in 1951, the rippled β-sheet was hypothesized by the same authors in 1953. Abstract : Following the seminal theoretical work on the pleated β-sheet published by Pauling and Corey in 1951, the rippled β-sheet was hypothesized by the same authors in 1953. In the pleated β-sheet the interacting β-strands have the same chirality, whereas in the rippled β-sheet the interacting β-strands are mirror-images. Unlike with the pleated β-sheet that is now common textbook knowledge, the rippled β-sheet has been much slower to evolve. Much of the experimental work on rippled sheets came from groups that study aggregating racemic peptide systems over the course of the past decade. This includes MAX1/DMAX hydrogels (Schneider), L/D-KFE8 aggregating systems (Nilsson), and racemic Amyloid β mixtures (Raskatov). Whether a racemic peptide mixture is "ripple-genic" ( i.e., whether it forms a rippled sheet) or "pleat-genic" ( i.e., whether it forms a pleated sheet) is likely governed by a complex interplay of thermodynamic and kinetic effects. Structural insights into rippled sheets remain limited to only a very few studies that combined sparse experimental structural constraints with molecular modeling. Crystal structures of rippled sheets are needed so we can rationally design rippled sheet architectures. Here we report a high-resolution crystal structure, in which (l, l, l )-triphenylalanine and (d, d, d )-triphenylalanine form dimeric antiparallel rippled sheets, which pack into herringbone layer structures. The arrangements of the tripeptides and their mirror-images in the individual dimers were in excellent agreement with the theoretical predictions by Pauling and Corey. A subsequent mining of the PDB identified three orphaned rippled sheets among racemic protein crystal structures.